Photovoltaic Based Automatic Rice Thresher Machine To Help Farmers in Pandemi Covid-19 - Ilmi Rizki Imaduddin; Hendra Wahudi; Nurul Hamid; Mahmud Pribadi; Muhammad Mahros (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
The rice thresher machine is an important part of the rice processing process. Before the harvesting process, the rice fields are drained for 7-10 days before the harvest period by using a sharp sickle to cut the base of the stems, then the harvest is stored in a container or lined place. The low application of cultivation technology can be seen from the large potential gap between production. With the creation of this system, the process of threshing rice from the stalks can be done automatically, so that this system is expected to be able to provide the process of threshing rice from the stalks to be faster, easier, more efficient and safe for workers. data from the presentation of rice tresher slender yields 223.17 S, at puly rpm the average value produced is 32.82 S, with an average voltage of 11 V and an average current of 0.18 A. 9.13 minutes, with initial grain weight of 15 kg with an average threshing yield of 6.6 kg, with a threshing capacity of 42.2 kg / hour. And the current and voltage data on the solar panel and the resulting charging, the highest voltage is 12 V with a current of 1.69 A which occurs at 12.30 Wib.